Multisystem Langerhans cell histiocytosis coexisting with metastasizing adenocarcinoma of the lung: A case report - Lovrenski, Aleksandra; Djurić, Mirna; Klem, Ištvan; Eri, Živka; Panjković, Milana; Tegeltija, Dragana; Považan, Djordje (Vojnosanitetski pregled, 2017)
Introduction. Langerhans cell histiocytosis (LCH) is an uncommon disease of unknown etiology characterized by uncontrolled proliferation and infiltration of various organs by Langerhans cells. Case report. We presented a 54-year-old man, heavy smoker, with dyspnea, cough, hemoptysis, headache and ataxia, who died shortly after admission to our hospital. On the autopsy, tumor was found in the posterior segment of the right upper pulmonary lobe as well as a right-sided occipitoparietal lesion which penetrated into the right ventricle resulting in internal and external hematocephalus. Histologically and immunohistohemically, the diagnosis of primary lung adenocarcinoma with brain metastasis was made (tumor cells showed positivity for CK7 and TTF-1 which confirmed the diagnosis). In the lung parenchyma around the tumor, as well as in brain tissue around the metastatic adenocarcinoma histiocytic lesions were found. Light microscopic examination of the other organs also showed histiocytic lesions involving the pituitary gland, hypothalamus, spleen and mediastinal lymph nodes. Immunohistochemical studies revealed CD68, S-100 and CD1a immunoreactivity within the histiocytes upon which the diagnosis of Langerhans' cells histiocytosis was made. Conclusion. The multisystem form of LCH with extensive organ involvement was an incidental finding, while metastatic lung adenocarcinoma to the brain that led to hematocephalus was the cause of death.   Key words histiocytosis, langerhans-cell; diagnosis; lung neoplasms; adenocarcinoma; immunohistochemistry.
Keywords: Neoplasm Metastasis; Langerhans Cells; Histiocytosis; Adenocarcinoma